A glimpse into the future: can we learn lessons from the pandemic? - Pullen, Lara C. (Am J Transplant, 2020)
This month’s installment of “The AJT Report” explores several ways in which COVID-19 may be presenting opportunities for creating meaningful change for the transplant community and the US health system as a whole.